A imortalidade da alma no Kitāb Al-Nāfs (Livro da alma) de Ibn Sīnā (Avicena) - Pereira, Evandro Santana (2015)
The current dissertation is a study concerning the immortality of the soul, following the doctrine presented in the Book of the Soul of Ibn Sina. In Chapter I, primary sources are used in order to establish a philosophical biography of the philosopher, in which are presented the political and cultural context of where he lived, the more relevant facts and issues of his life, in addition to his principal works. In Chapter II, there is a short description of the Arabian Philosophy – the falsafa –, and an analysis of the major inheritances received by the philosopher: Plato, Aristotle, Plotinus and Al-Farabi, and of some works and concepts of these. Next, the avicennian philosophical system is studied, in order to establish an indispensable theory base to explain the individual immortality of the human soul in the Book of the Soul. This analysis starts with his Metaphysics, with the notions of necessary existent and contingent existent, and the essence/existence distinction; passes through his Cosmology, with the emanation of the cosmic intelligences from the necessary existent down to the sublunary world, where man is; and reaches its Psychology, in which man is capable of uniting himself with the active intelligence, by the means of his intellective faculty. After that, comments are made about the influence of Ibn Sina in the History of Philosophy. In Chapter III, the Book of Healing and the Book of the Soul are described. Following that, the soul is analyzed in his homonym book, with his proving, definition, substantiality and faculties. In more detail, the question of the immortality of soul is studied in its particularities, foremost in Sections 2 and 4 of Chapter Five of the book in light.